The Hypocrisy of Value and the Fight Against Corruption - UMOTONG , Iniobong (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
Corruption has consistently taken centre stage in conferences and public discourse, and the rationale behind this phenomenon is readily discernible. The pervasive impact of corruption on the stunted development of nearly every sector of the Nigerian economy can be directly attributed to the values that underpin it. It is well established that individuals collectively constitute the government, making it imperative to recognise that issues pertaining to institutional values are inherently linked to the individual values of those who govern these institutions. These individuals are products of the society they inhabit, shaped by the societal influences they are exposed to, and in turn, they influence the institutional values that govern the conduct of citizens. Therefore, there exists a compelling need to overhaul our value parameters. Drawing upon existing literature and the numerous discussions aimed at addressing this multifaceted social problem, it can be deduced that eradicating corruption is attainable. However, this study highlights the paradox of verbally condemning corruption with a plethora of anti-corruption slogans and agencies while concurrently embracing it both collectively and individually. The research identifies the individual as the battleground for the anti-corruption war and advocates a return to a foundational value reorientation, with leaders leading the charge, as an essential strategy for prevailing in the battle against corruption.